2021
DOI: 10.1136/bmjsem-2021-001164
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities in athletes after SARS-CoV-2 infection: a systematic review

Abstract: ObjectivesQuantification of pericardial/myocardial involvement and risks of sudden cardiac arrest/sudden cardiac death (SCA/SCD) after SARS-CoV-2 infection in athletes who return to sports.DesignSystematic review on post-SARS-CoV-2 infection pericardial/myocardial manifestations in athletes.Data sourcesCombinations of key terms in Medline, Embase and Scopus (through 2 June 2021).Eligibility criteria for selecting studiesInclusion: athletes, with cardiovascular magnetic resonance (CMR) or echocardiography after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 39 publications
(44 reference statements)
3
40
1
2
Order By: Relevance
“…Finally, almost all studies assessed hs-TN levels, but none showed a correlation with the presence of cardiovascular abnormalities. This finding confirmed what was pointed out by a recent systematic review [ 11 ], thus confirming that hs-TN changes may be related to a broad set of clinical reason. A recent review [ 51 ] showed that normal ranges in athletes are still poorly defined, and further studies are needed to assess the normal TN value in athletes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, almost all studies assessed hs-TN levels, but none showed a correlation with the presence of cardiovascular abnormalities. This finding confirmed what was pointed out by a recent systematic review [ 11 ], thus confirming that hs-TN changes may be related to a broad set of clinical reason. A recent review [ 51 ] showed that normal ranges in athletes are still poorly defined, and further studies are needed to assess the normal TN value in athletes.…”
Section: Discussionsupporting
confidence: 91%
“…At the beginning of the pandemic, cases of myocarditis had been frequently described in hospitalized patients, but no information was available regarding cardiac involvement in athletes [ 5 ]. As assessed in a recent systematic review, several studies have subsequently investigated the possible cardiovascular complications of COVID-19 infection in young athletes [ 11 ]. This because myocarditis is recognized as a cause of sudden death in athletes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many important aspects of COVID-19 in sport, but given that the virus has emerged recently, practical knowledge is rather limited. Numerous studies have been published with the aim of giving instructions and guidelines on the treatment of athletes during and after infection [ 18 , 19 , 21 , 33 , 34 ]. As mentioned in the introduction, RTP protocols have been developed and were created based on prior knowledge of viral infections that attack the cardiorespiratory system [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been published with the aim of giving instructions and guidelines on the treatment of athletes during and after infection [ 18 , 19 , 21 , 33 , 34 ]. As mentioned in the introduction, RTP protocols have been developed and were created based on prior knowledge of viral infections that attack the cardiorespiratory system [ 21 , 34 ]. However, there is a clear lack of research on concrete examples of infected athletes.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 5 out of 1,597 athletes (0.3%) had both symptoms associated with myocarditis and abnormal laboratory (troponin level) and/or imaging findings (electrocardiography (ECG) and/or echocardiography) [ 18 ]. In a systematic review of CMR imaging studies performed in athletes with a history of COVID-19, the proportion of athletes with a confirmed diagnosis of myocarditis varied between 0% and 15% [ 19 ]. In the general population, data on the occurrence of subclinical myocarditis and pericarditis after COVID-19 are lacking.…”
Section: Myocarditis Pericarditis and Covid-19mentioning
confidence: 99%